Improving healthcare quality for transgender patients in the perioperative setting: The patient's perspective. Issue 6 (June 2023) - McAuliffe, Megan; Baker, Deborah; D'Aoust, Rita
Transgender individuals reported higher rates of discrimination and barriers to care within healthcare settings than their cisgender counterparts. There is a paucity of literature concerning the barriers experienced within perioperative healthcare settings. Participants completed a sociodemographic questionnaire and a 7-item Likert-type scale survey: the Everyday Discrimination Scale Adapted for Medical Settings. Overall, 57% of trans-individuals who underwent gender-affirming surgery reported perceptions of discrimination when interacting with healthcare providers within the perioperative setting according to responses from the Discrimination in Medical Settings Survey. There was an overall difference in the summary scores between participants based on gender transition. These findings highlight an opportunity to address barriers to care related to discrimination and negative patient–provider interactions. These findings have implications for the development and integration of patient-informed, evidence-based, trans-specific, educational and cultural competency trainings to enhance the healthcare professional's knowledge, attitudes, comfort and ability to care for the transgender population. Key phrases: Transgender individuals reported higher rates of discrimination and barriers to care; enhancing the healthcare professional's knowledge, attitudes, comfort and ability to care for the transgender population; opportunities to address barriers to care related to discrimination and negative patient–provider interactions; individuals who transitioned from male-to-female (MTF) had higher scores related to perceptions of discrimination during interactions with healthcare providers.